Arctic business potential from Oulu region's perspective – opportunities and obstacles - Niemelä, Sami; Hintsala, Henna (Oulun ammattikorkeakoulu, 2016)
The future of the Arctic and the prospective Arctic business opportunities have been studied from Oulu region’s perspective in two separate projects. Observations from these projects form the core of this article. Conceptualisation of the Arctic is a crucial precondition when processing Arctic themes and topics. The Arctic can be interpreted as special conditions and operations and know-how related to them or the Arctic can be defined as a location of various economic activities related to Arctic resources. It is suggested that by focusing on the strategic significance, networking by creating business-oriented clusters and increasing visibility by highlighting and promoting Arctic expertise it would be possible to clarify Arctic concepts and business opportunities. Versatile information presented in approachable and illustrative form should be combined with appropriate promotion of the different aspects of the Arctic. The gap between public policy and private sector actions should be narrowed with all means possible.